1997
DOI: 10.1007/s004670050281
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal recessive polycystic kidney disease: long-term outcome of neonatal survivors

Abstract: Autosomal recessive polycystic kidney disease causes renal and hepatic dysfunction in childhood. We describe the clinical outcome of 52 children with this diagnosis born between 1950 and 1993. Currently 23 are alive, 24 dead and 5 have been lost to follow-up; 1 has been dialysed and 7 transplanted. Life-table analysis of the patients surviving the 1st month of life revealed an actuarial renal survival of 86% at 1 year and 67% at 15 years. The probability of requiring anti-hypertensive treatment was 39% at 1 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
134
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(143 citation statements)
references
References 23 publications
4
134
0
5
Order By: Relevance
“…4,13 Therefore, liver and kidney serum parameters were measured in wild-type and Pkhd1ex40-mutated mice. We found that the mean values and standard deviation of serum creatinine, phosphate, potassium, creatine kinase, urea, glutamic oxaloacetic acid, glutamic pyruvic transaminase, alkaline phosphatase, gamma-glutamyltransferase, total protein, and bilirubin values when measured at different ages between 8 weeks to 14 months did not differ between wildtype and homozygous mutant littermates (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,13 Therefore, liver and kidney serum parameters were measured in wild-type and Pkhd1ex40-mutated mice. We found that the mean values and standard deviation of serum creatinine, phosphate, potassium, creatine kinase, urea, glutamic oxaloacetic acid, glutamic pyruvic transaminase, alkaline phosphatase, gamma-glutamyltransferase, total protein, and bilirubin values when measured at different ages between 8 weeks to 14 months did not differ between wildtype and homozygous mutant littermates (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…In ARPKD patients surviving the neonatal period, the prognosis is more optimistic, and the disease phenotypes may vary significantly. 4 Frequent complications include systemic hypertension, end-stage renal disease, and portal hypertension resulting from congenital hepatic fibrosis.…”
mentioning
confidence: 99%
“…1 The clinical spectrum is variable with ϳ30 to 50% of affected neonates dying shortly after birth and other patients surviving to adulthood. [2][3][4] The most severely affected fetuses have enlarged echogenic kidneys in utero with associated oligohydramnios indicative of intrauterine renal failure. Neonatal demise in this setting is primarily attributable to respiratory failure from associated pulmonary hypoplasia.…”
mentioning
confidence: 99%
“…These individuals present later with a spectrum of associated morbidities that include systemic and portal hypertension, congenital hepatic fibrosis, and progressive renal insufficiency. 3,5 Primary organ system involvement in the latter presentation of human ARPKD is restricted to the liver and kidneys, and the most common pathological lesions seen are biliary dysgenesis accompanied by portal tract fibrosis in the liver and fusiform dilatations of the renal collecting ducts radiating from the medulla to the cortex of the kidney.…”
mentioning
confidence: 99%
“…Las tasas de supervivencia son aproximadamente de 86% a los cinco años, 67 a 71% a los 10 años. [7][8][9][10][11][12] La hipertensión arterial es diagnosticada al nacimiento en 80% de los pacientes. 8 Sin embargo, en nuestro paciente, ni al nacimiento ni a la entrada del hospital, se documentó hipertensión arterial; ésta fue detectada de manera súbita y sin presencia de manifestaciones clínicas.…”
Section: Discussionunclassified